Efficacy of Anti-Amyloid Monoclonal Antibody Immunotherapy on Cognitive Progression in Alzheimer's Disease Patients : A Systematic Review of Randomized Controlled Trials and Primary Studies - Luh Wayan Puspa Ningsih; Ida Bagus Kade Satyagraha (International Medical Journal Corp. Ltd, 2026)
Introduction: Alzheimer's disease (AD) is the leading cause of dementia worldwide, with the amyloid cascade hypothesis implicating amyloid-beta (Aβ) accumulation as a primary pathogenic driver. Anti-amyloid monoclonal antibodies (mAbs) represent the most advanced class of disease-modifying therapies, yet their cognitive efficacy, safety profile, and clinical meaningfulness remain subjects of ongoing debate. This systematic review synthesizes evidence from randomized controlled trials (RCTs) evaluating anti-amyloid mAb immunotherapy across all agents and disease stages. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Eligible studies comprised Phase II and III placebo-controlled RCTs evaluating anti-amyloid mAbs in patients with mild cognitive impairment or mild-to-moderate AD. Primary outcome was change in Clinical Dementia Rating-Sum of Boxes (CDR-SB). Risk of bias was assessed using Cochrane RoB 2.0. Results: Twenty publications representing 15 distinct trials (N>36,000 participants) evaluating seven mAbs were included. Second-generation mAbs (lecanemab, donanemab) demonstrated statistically significant CDR-SB slowing (lecanemab: Δ–0.45, 95% CI –0.67 to –0.23, p<0.001, 27% slowing; donanemab: Δ–0.67, 95% CI –0.95 to –0.40, p<0.001, 36% slowing) with corresponding amyloid PET reduction. First-generation agents (bapineuzumab, solanezumab, crenezumab, gantenerumab) failed to demonstrate clinically meaningful cognitive benefit despite variable amyloid clearance. Amyloid-related imaging abnormalities (ARIA) occurred in 12.6–41.3% of treated participants, with APOE ε4 homozygosity as the strongest risk factor. Quality-of-life and caregiver burden outcomes favored lecanemab and donanemab. Discussion: Divergent efficacy between mAb generations reflects differential Aβ species targeting, with second-generation agents selectively targeting pathogenic protofibrils and pyroglutamate-modified Aβ. The clinical meaningfulness of statistical differences remains debated as minimal clinically important differences may not be achieved within 18-month trial windows. ARIA necessitates mandatory MRI monitoring, and strict eligibility criteria limit real-world generalizability to <15% of AD populations. Conclusion: Second-generation anti-amyloid mAbs, particularly lecanemab and donanemab, represent the first disease-modifying therapies demonstrating statistically significant cognitive slowing in early AD. However, absolute benefit remains modest, safety monitoring is mandatory, and population eligibility is substantially restricted. Long-term evidence beyond 18 months and head-to-head trials are needed.